Influência do silício na intensidade da antracnose, na composição química e na qualidade das sementes de feijoeiro - Veiga, André Delly (2008)
In this work, the influence of silicon fertilization on the physiological, sanitary and chemical quality, the enzyme activity, the anthracnose intensity and on the structural intensity of bean seeds was evaluated. The research was developed in the Analysis and Biotechnology Laboratories of Seed Sector, in the experimental area of the Agriculture Department, in the seed pathology laboratory of the Phytopathology Department and in the Plant Anatomy laboratory of the Biology Department of the UFLA. Bean seeds of the cultivar BRS MG Majestoso were produced under 5 doses of leaf application of Supa Potássio®(0; 0.8; 1.6; 2.4 and 3.2 L . ha-1), which possesses 20% of SiO2 and 15% of K2O, and in the presence and absence of the fungus Colletotrichum lindemuthianum. The experimental design was the one of randomized blocks in split plot with four replicates, more one additional treatment, in the plot with fungus, the plants being sprayed with the fungicide Dithane®. Germination, sanitary quality by blotter test, electric conductivity, dry matter of seedlings, the activity of the enzymes esterase, peroxidase and superoxide dismutase and potassium leaching were evaluated. Further, the paper roll germination for detection of C. lindemuthianum, the determination of the lignin content and the content of macro and micronutrients in leaves and seeds, the morphologic report in light microscopy and the evaluation of anthracnose severity on leaves and pods were accomplished. Seeds produced under 3.2 L . ha-1 of Supa Potássio® present larger thickness of the seedcoat. Seeds produced under 3.2 L . ha-1 of Supa Potássio® present reduced incidence of the fungus C. Lindemuthianum. The zinc content in seeds is influenced by the fertilization with silicon via foliar.The nitrogen content in leaves is increased by the fertilization with silicon via foliar. The contents of calcium and magnesium in seeds are influenced by the presence of the fungus C. lindemuthianum. The application of silicon on bean plants decrease the intensity of the attack by the fungus Colletotrichum lindemuthianum both in leaves and in pods and provides less incidence of Fusarium in bean seeds. The activity of the enzymes esterase, peroxidase and superoxide dismutase, germination and potassium leaching of bean seeds are not affected by the addition of silicon via.